MICROALGAE AS A SUSTAINABLE FACADE FOR OCCUPANTS’ HEALTH: A REVIEW - Livia Hariyanto; Lilianny Sigit Arifin; Rully Damayanti (Petra Christian University, 2022)
Facade as a sustainable strategy can provide energy-efficient solutions. Some designers' knowledge of the sustainable paradigm is incomplete, resulting in façade components that are harmful to occupants' health. The development of facade microalgae can be a sustainable facade solution. The purpose of this study is to examine the microalgae façade with the parameters of Strategies for Sustainable Architecture: Health by Paola Sassi through an analysis of the space comfort and the materials used. The research method is qualitative with a descriptive type of research from previous research articles and journals that discuss the microalgae facade. The results showed that the microalgae facade provides optimal quality of space comfort with materials that decrease pollution. According to the findings, microalgae facades as a sustainable strategy for occupant health and the environment. The microalgae facade as green technology is not only for building performance but also for the health of building occupants.